The Ethanol Extract of Zingiber zerumbet Attenuates Streptozotocin-Induced Diabetic Nephropathy in Rats - Tzeng, Thing-Fong (Hindawi Publishing Corporation, 2013)
The ethanol extract from the rhizome of Zingiber zerumbet (L.) Smith (EEZZR) has been indicated to possess an insulin-like property by ameliorating hyperglycemia in diabetes. We aimed to investigate whether EEZZR exerts an ameliorative effect on renal damage in diabetes induced by streptozotocin (STZ). Diabetic rats were treated orally with EEZZR (200 and 300 mg kg(−1) per day) or metformin (100 mg kg(−1) per day) for 8 weeks. The plasma glucose, creatinine, and blood urea nitrogen as well as urine protein levels and the ratio of kidney weight to body weight were significantly elevated in diabetic rats. EEZZR displayed similar characteristics to those of metformin in reducing hyperglycemia and renal dysfunction in diabetic rats. The histological examinations revealed amelioration of diabetes-induced glomerular pathological changes following the treatment with EEZZR. In addition, the protein expressions of renal nephrin and podocin in diabetic rats were significantly increased following the treatment with EEZZR. The AMP-activated protein kinase (AMPK) protein phosphorylation and expression levels were remarkably reduced in diabetic renal tissues. EEZZR treatment significantly rescued the AMPK phosphorylation compared to nontreated diabetic group. This study suggested that the renoprotective effects of EEZZR may be similar, with the action of metformin, to the prevention of AMPK dephosphorylation and upregulate the expressions of renal nephrin and podocin.